Proceedings of the 2016 International Conference on Biological Engineering and Pharmacy (BEP 2016) 2017
DOI: 10.2991/bep-16.2017.3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Light Quality on The Quality Formation of Tomato Fruits

Abstract: Abstract-The effects of light quality on the quality formation of tomato (cv. MicroTom) fruits were studied in controlled-environment house. There were 4 LEDs treatments: the ratio of red (660nm): blue (460nm) was 1:1 (1R1B), 2:1 (2R1B), 4:1 (4R1B) and 8:1 (1R1B), the Photosynthetic Photon Flux Density (PPFD) was 300µmol· m -1 s -1 and illumination time was 6:00 -18:00, the quality of tomato fruits were determined at 30, 45 and 60 days after anthesis (DAA). The contents of soluble protein, free amino acid, fla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 22 publications
2
6
0
Order By: Relevance
“…Increased accumulation of plant metabolites (e.g., soluble sugars) was observed in the presence of red-blue LED. Natural daylight supplemented with red-blue LEDs increased the soluble sugars and organic acids in different crops (Samuolienė et al 2012b;Lin et al 2013;Samuolienė et al 2013;Dong et al 2014;Choi et al 2015;Xie et al 2016;Hasan et al 2017). In melon, Cui et al (2017) showed red:blue LED to be the most effective in increasing soluble sugar content.…”
Section: ____________________________________________________________________________________________________________________mentioning
confidence: 99%
See 1 more Smart Citation
“…Increased accumulation of plant metabolites (e.g., soluble sugars) was observed in the presence of red-blue LED. Natural daylight supplemented with red-blue LEDs increased the soluble sugars and organic acids in different crops (Samuolienė et al 2012b;Lin et al 2013;Samuolienė et al 2013;Dong et al 2014;Choi et al 2015;Xie et al 2016;Hasan et al 2017). In melon, Cui et al (2017) showed red:blue LED to be the most effective in increasing soluble sugar content.…”
Section: ____________________________________________________________________________________________________________________mentioning
confidence: 99%
“…Blue LEDs (450-470 nm) combined with red LEDs also increased the photosynthetic capacity and plant biomass in tomato, cucumber and pepper transplants (Hernández & Kubota 2012;Samuolienė et al 2012a). Furthermore, single or mixed blue and red LEDs improved the quality and yield of vegetables and fruit when compared with white fluorescent or solar light (Hao et al 2012;Dong et al 2014;Choi et al 2015;Li et al 2016;Xie et al 2016;Nadalini et al 2017). As blue and red light control the rates of photosynthesis through the opening and/or closing of stomata, their effect on plant biomass or yield was anticipated (Sabzalian et al 2014).…”
Section: Introductionmentioning
confidence: 98%
“…Although there are many reports on light regulating lycopene accumulation, how blue light affects lycopene content in undetached tomato is not well understood. The only observation worthy of mention in this regard is that the over expression of the blue light receptor CYR1a resulted in elevated lycopene content in tomato (Liu et al 2017), and that lycopene content continuously increased from 45 to 60 days after anthesis under 2R1B treatment, i.e., when the red (660 nm):blue (460 nm) ratio was 2:1 (Xie et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Among the different LEDs, red LED irradiation enhanced β-carotene accumulation in pea plants [ 84 ]. Other studies reported that red LED irradiation resulted in an increase in β-cryptoxanthin content in citrus fruits [ 156 ] and lycopene content in tomatoes [ 157 ]. The duration of LED irradiation affected total carotenoid content and carotenoid biosynthesis in the growing plants.…”
Section: Resultsmentioning
confidence: 99%